(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
This experiment was carried out to analyze the effects of CCB (chromate-copper-boron) preservative treatment on physical and mechanical properties of Albizia richardiana wood using dipping method. Retention of preservative was maximum at 8% concentration of the preservatives. Based on the retention at this concentration, the physical and mechanical properties of the treated wood were examined. The density of untreated A. richardiana wood was 521 kg/m3. It changed to 542 kg/m3 on treatment. This increase in density by 2.30% for treated wood was significant. On the other hand, modulus of rupture (MOR) increased significantly from 93 to 107 N/mm2 on treatment of the wood. The modulus of elasticity (MOE) increased from 3205 to 4861 N/mm2. Physical and mechanical properties of the wood improved by treating with CCB preservative. Bangladesh J. Sci. Ind. Res. 50(3), 189-192, 2015